Reasons for Home Schooling in Canada - Arai, A. Bruce (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
Why do parents in Canada choose to home school their children? This article presents the results of qualitative interviews with 23 home-schooling families in Ontario and British Columbia and compares these results with previous research in other jurisdictions, particularly the United States. The findings suggest that Canadian home-based educators have very different reasons for choosing home schooling than their U.S. counterparts. Possible explanations for these differences are discussed. Dans cet article, l’auteur présente les résultats d’entrevues qualitatives auprès de 23 familles de l’Ontario et de la Colombie-Britannique qui ont opté pour l’ensei- gnement à domicile et compare ces résultats avec ceux de recherches menées aux États-Unis. Il semble que les parents canadiens n’aient pas du tout les mêmes raisons d’opter pour l’enseignement à domicile que les parents américains. L’auteur propose des explications.